Abdominal imaging - Sahani, Dushyant V; Samir, Anthony E (Maryland Heights, Mo. : Saunders/Elsevier, 2011)
Drs. Dushyant Sahani and Anthony Samir, is a comprehensive 2-volume reference that encompasses both GI and GU radiology. It provides richly illustrated, advanced guidance to help you overcome the full range of diagnostic, therapeutic, and interventional challenges in abdominal imaging and combines an image-rich, easy-to-use format with the greater depth that experienced practitioners need. Select the best imaging approaches and effectively interpret your findings by comparing them to thousands of images that represent every modality and every type of abdominal imaging. Find detailed, expert guidance on all diagnostic, therapeutic, and interventional aspects of abdominal imaging in one authoritative source, including challenging topics such as Oncologic Assessment of Tumor Response and How to Scan a Difficult Patient. Efficiently locate the information you need with a highly templated, well-organized, at-a-glance organization. Better evaluate GI/GU conditions with thousands of high-quality digital images
Imaging techniques -- Nontraumatic acute abdomen -- Stomach -- Small bowel and colon -- Liver and pancreas -- Gallbladder, bile ducts, and spleen -- Abdominal and pelvic lymph nodes -- Urogenital imaging -- Abdominal wall and hernias
Includes bibliographical references and index
Keywords: Abdomen -- Imaging; Radioisotope scanning; Digestive System Diseases -- diagnosis; Abdomen -- diagnostic imaging; Abdomen -- physiopathology; Diagnostic Imaging -- methods; Radionuclide Imaging